Simulação e análise técnico-econômica do processo de bi-reforma do metano para produção do gás de síntese - Zarif, Francisco Goldenberg (Universidade Federal de São Carlos, 2021)
Considering the multiple uses syngas has as an intermediate for products with higher monetary value, it is natural that there should be a lot of effort to optimize its production. In this scenario, alternative chemical routes have been studied as substitutes to the traditional methane reforming, followed by its transformation into hydrogen and carbon monoxide, in order to guarantee the ideal proportion of each component to its main goal, whether in the production of fuels, ammonia, methanol or any other product that is derived from syngas. This study had the objective to study the bi-reforming process from methane prevenient from natural gas, one of the alternatives to the traditional reforming with the best results so far. In order to achieve this goal, a brief research about the state of the art of this process was made, followed by simulations using Aspen Plus V10©, with process conditions obtained from the literature. The results from the simulation were then combined with an economic analysis, which lead to conclusions about the economic viability of a bi-reforming industrial plant, as well as to proves regarding its advantages in comparison to other syngas production methods, with the main goal to contribute to the advances in this research field.
Simulation and techno-economic analysis of the bioreforming process of methane for syngas production
Keywords: bi-reforma; bireforming; metano; methane; simulação; Simulation; análise técnico-econômica; techno-economic analysis; ENGENHARIAS::ENGENHARIA QUIMICA